Assessing the Implementation of Islamic Studies Curriculum in North-West Nigeria: A Critical Review - Danzaria, Nasir; Aliyu Dada, Abdullahi (International Research-Based Education Journal, 2024)
The study is on the relevance of appropriate method in the implementation of the Islamic Studies curriculum in schools of Arabic and Islamic Studies in North-west Nigeria. It is a descriptive survey design with a population of one thousand three hundred and ninety-four (1,394) Islamic Studies teachers from the Senior Arabic and Islamic Studies schools in North-West Nigeria and with a sample of three hundred and six (306) Islamic Studies teachers.  Purposive sampling technique was used in selecting the sample States for the study using multistage cluster sampling process where Katsina, Kano, Kaduna and Jigawa states due to fewer security challenges in the states compared to the remaining three States (Zamfara, Sokoto and Kebbi). The States were clustered according to zonal education offices where simple random sampling technique was used in selecting the schools and respondents from the clustered zones. The instrument used was developed by the researchers designed in four-point moderated Likert rating scale to suit the objective of the study. The study comprised of one research question and one hypothesis. The research question was answered by mean score while the hypothesis was analysed through the t-test statistics. The findings revealed that Islamic Studies teachers appropriately used suitable method in the implementation of the Islamic studies curriculum in the schools of Arabic and Islamic studies in North-West Nigeria. It is recommended that teachers in the schools of Arabic and Islamic Studies should maintain the use of learner - centred, demonstration and problem-solving approaches in the teaching and learning process because of their positive effects in teaching and learning process.